Prevalence and characterization of plasmids carrying sulfonamide resistance genes among Escherichia coli from pigs, pig carcasses and human - Shuyu Wu; Anders Dalsgaard; Anette M. Hammerum; Lone Jannok Porsbo; Lars Jensen (2010)
Abstract Background Sulfonamide resistance is very common in Escherichia coli . The aim of this study was to characterize plasmids carrying sulfonamide resistance genes ( sul1 , sul2 and sul3 ) in E. coli isolated from pigs and humans with a specific objective to assess the genetic diversity of plasmids involved in the mobility of sul genes. Methods A total of 501 E. coli isolates from pig feces, pig carcasses and human stools were tested for their susceptibility to selected antimicrobial. Multiplex PCR was conducted to detect the presence of three sul genes among the sulfonamide-resistant E. coli isolates. Fifty-seven sulfonamide-resistant E. coli were selected based on presence of sul resistance genes and subjected to conjugation and/or transformation experiments. S1 nuclease digestion followed by pulsed-field gel electrophoresis was used to visualize and determine the size of plasmids. Plasmids carrying sul genes were characterized by PCR-based replicon typing to allow a comparison of the types of sul genes, the reservoir and plasmid present. Results A total of 109/501 isolates exhibited sulfonamide resistance. The relative prevalences of s ul genes from the three reservoirs (pigs, pig carcasses and humans) were 65%, 45% and 12% for sul2 , sul1 , and sul3 , respectively. Transfer of resistance through conjugation was observed in 42/57 isolates. Resistances to streptomycin, ampicillin and trimethoprim were co-transferred in most strains. Class 1 integrons were present in 80% of s ul1 -carrying plasmids and 100% of sul3 -carrying plasmids, but only in 5% of sul2 -carrying plasmids. The sul plasmids ranged from 33 to 160-kb in size and belonged to nine different incompatibility (Inc) groups: FII, FIB, I1, FIA, B/O, FIC, N, HI1 and X1. IncFII was the dominant type in sul2 -carrying plasmids (52%), while IncI1 was the most common type in sul1 and sul3 -carrying plasmids (33% and 45%, respectively). Multireplicons were found associated with all three sul genes. Conclusions Sul genes were distributed widely in E. coli isolated from pigs and humans with sul2 being most prevalent. Sul -carrying plasmids belonged to diverse replicon types, but most of detected plasmids were conjugative enabling horizontal transfer. IncFII seems to be the dominant replicon type in sul2 -carrying plasmids from all three sources.